Sintesis Katalis Platina-Titanium Dioksida Didukung Vulcan XC-72 dan Karakterisasinya Menggunakan Pengujian Cyclic Voltammetry - Situmorang, Amelia; Joni, Made; Suarda, Made; Astawa, Ketut; Sucipta, Made (Teknik Desain Mekanika, 2024)
Abstract Replacing fossil fuels with hydrogen energy is a solution to reduce environmental problems and the increasing demand for fossil fuel energy. The electrical power generated by hydrogen energy can use a Proton Exchange Membrane Fuel Cell (PEMFC), one of the main components of which is a catalyst to facilitate the reaction. The main objective of this research is to reduce the use of platinum as the main catalyst material by synthesizing platinum, TiO2, and Vulcan XC-72 materials which are varied in mass on three catalyst samples. Catalyst synthesis was prepared through two methods, namely hydrothermal and photo-deposition methods. The synthesized catalysts were subjected to a cyclic voltammetry (CV) test to determine the current response to potential. The result will indicate that the catalyst is suitable for use in PEMFC. From the mass variation in the catalyst samples, it was found that Sample 3 with the highest mass of platinum showed the best results in the CV test, which had the highest current peak of the other catalyst samples. Keywords: Catalyst, PEMFC, Synthesis, Cyclic Voltammetry Test.